2022
DOI: 10.12973/ijem.8.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Internal Locus of Control and Entrepreneurial Intentions of College Students: A Chain Mediation Model

Abstract: <p style="text-align: justify;">This study explores the relationship among the internal locus of control, entrepreneurial alertness, entrepreneurial opportunity recognition, and entrepreneurial intentions of college students. The scales of internal locus of control, entrepreneurial alertness, entrepreneurial opportunity recognition, and entrepreneurial intention have been used to conduct a questionnaire survey among 921 undergraduates from four universities in China. The results show four key findings. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Entrepreneurial attitude is a psychological dimension that plays a key role in predicting students' intention in entrepreneurship (Hassi, 2016;Wongnaa & Seyram, 2014). Empirical research has shown that a positive entrepreneurial attitude can increase one's entrepreneurial intentions (Hou et al, 2019;Wang & Huang, 2022). Students who have a good entrepreneurial attitudes tend to be more confident in developing their own business.…”
Section: Entrepreneurial Attitudesmentioning
confidence: 99%
“…Entrepreneurial attitude is a psychological dimension that plays a key role in predicting students' intention in entrepreneurship (Hassi, 2016;Wongnaa & Seyram, 2014). Empirical research has shown that a positive entrepreneurial attitude can increase one's entrepreneurial intentions (Hou et al, 2019;Wang & Huang, 2022). Students who have a good entrepreneurial attitudes tend to be more confident in developing their own business.…”
Section: Entrepreneurial Attitudesmentioning
confidence: 99%
“…The SEB is conceptualized as a means of identifying and acknowledging prospective opportunities and subsequently translating these ideas into actionable steps (Wang and Huang, 2022). Furthermore, Gieure et al (2020) revealed that the SEI is subject to influence by the presence of entrepreneurial talents.…”
Section: Student Entrepreneurial Behavior and Student Entrepreneurshi...mentioning
confidence: 99%
“…Entrepreneurial alertness, assists the strategic adaptability of the organization by improving its capacity to react swiftly to environmental changes through the adoption of competitive procedures (Cui et al, 2016). It opens opportunities and can unearth those that others overlook with great synergy, is found to be a significant driver of entrepreneurial intent (Wang and Huang, 2022). This mind-set is characterized by developing plans, continuously scanning the environment, and being fully prepared at any time.…”
Section: The Importance Of Entrepreneurial Alertnessmentioning
confidence: 99%